2010
DOI: 10.5483/bmbrep.2010.43.4.268
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of polyphenols isolated from Rhus verniciflua on Aldo-keto reductase family 1 B10

Abstract: Aldo-keto reductase family 1 B10 (AKR1B10) is a member of the NADPH-dependent aldo-keto reductase (AKR) superfamily, and has been considered to be a potential cancer therapeutic target. Total extract from the bark of Rhus verniciflua (Toxicodendron vernicifluum (Stokes)) showed AKR1B10 inhibitory activity. To identify the active compounds from R. verniciflua responsible for AKR1B10 inhibition, nine compounds were isolated via bioactivity-guided isolation and tested for their effects against recombinant human A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Cys299 is located close to the active site and modulates the interaction Given the important implications of AKR1B10 in tumor development and cancer chemoresistance, the search for inhibitors of this enzyme is a thriving area of research. Several compounds have been found to display AKR1B10 inhibitory properties in vitro, including some nonsteroidal anti-inflammatory drugs (41), butein (42), and curcumin derivatives (43). Our results suggest that PGA-type cyPG may constitute a novel class of AKR inhibitors.…”
Section: Discussionmentioning
confidence: 70%
“…Cys299 is located close to the active site and modulates the interaction Given the important implications of AKR1B10 in tumor development and cancer chemoresistance, the search for inhibitors of this enzyme is a thriving area of research. Several compounds have been found to display AKR1B10 inhibitory properties in vitro, including some nonsteroidal anti-inflammatory drugs (41), butein (42), and curcumin derivatives (43). Our results suggest that PGA-type cyPG may constitute a novel class of AKR inhibitors.…”
Section: Discussionmentioning
confidence: 70%
“…Compounds isolated from R. verniciflua showed potent inhibitory effects on AKR1B1 and AKR1B10 [106,107]. Song et al [28] reported that butein (19) extracted from R. verniciflua was a potent uncompetitive inhibitor for AKR1B10 and its inhibition pattern was the same as that found against AKR1B1 [106], although its potency against AKR1B1 was slightly higher. Numerous former studies have indicated that human bladder carcinoma and hepatoma could also be suppressed by butein through various mechanisms [108,109].…”
Section: Natural-based Derivativesmentioning
confidence: 82%
“…The above substances were also reported to present antitumor properties [99][100][101][102], and the inhibition effect on AKR1B10 might be one of mechanisms on their anticancer activities. Other plant polyphenols, such as butein (WO2014081124) [103] isolated from Rhus verniciflua, a medicinal plant, and dicaffeoyl quinic acid (CN104710312) [104] were also reported to can inhibit AKR1B10 [28,105]. Compounds isolated from R. verniciflua showed potent inhibitory effects on AKR1B1 and AKR1B10 [106,107].…”
Section: Natural-based Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…A purified flavonoid fraction prepared from RVS was found to have effective antiproliferative and apoptotic activities on various tumor cell lines including human lymphoma, breast cancer, osteosarcoma and transformed hepatoma cells [4,5,33,34]. Among these compounds, butein (3,4,2′,4′-tetrahydroxychalone) and sulfuretin are also suggested to have therapeutic value in suppressing cancer growth [35]. However, a synergistic effect of gemcitabine and aRVS extract was not observed in our study.…”
Section: Discussionmentioning
confidence: 99%